PERAN PEMODERASI REPUTASI PERUSAHAAN PADA PENGARUH LUAS PENGUNGKAPAN WEBSITE CSR TERHADAP KINERJA KEUANGAN - Natasya Elvin Maharani; -, Erna Widiastuty (Jurnal Riset Akuntansi, 2024)
The objective of this research is to provide empirical evidence concerning the moderating role of firm reputation on the effect of the range of website CSR disclosure on firm financial performance. The study focused on companies within the manufacturing sector that are listed on the Indonesia Stock Exchange during the period from 2016 to 2022. This research used a purposive sampling method and 238 firm-year observations were obtained. The moderating variable is firm reputation measured by market capitalization ratio. The independent variable of the range of website CSR disclosure is measured using content analysis method and dependent variable is firm financial performance measured by ROA and ROE. Data were analyzed through methods such as multiple linear regression analysis methods and moderated regression analysis (MRA) test. The results provide empirical evidence that first, the range of website CSR disclosure has a negative and significant influence on the firm’s financial performance. Second, the results of this study provide empirical evidence that firm reputation was unable to moderate in the effect of the range of website CSR disclosure on firm financial performance.